Stabilization and Growth in an Open Islamic Economy. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
Islam proposes the replacement of an interest-based financial system with one which operates on the basis of risk and profit sharing. Using a general equilibrium model, this paper investigates some open-economy implications of the adoption of Islamic banking for growth and stabilization of the economy. It analyzes the long-run effects of Islamic banking on international capital flows and on the economy's capacity to adjust to disturbances. It concludes that monetary policy can be used effectively for stabilization purposes and that disturbances to asset positions are absorbed efficiently in an Islamic financial system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet